2005
DOI: 10.1007/s00280-005-0060-1
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator mass spectrometry allows for cellular quantification of doxorubicin at femtomolar concentrations

Abstract: Accelerator mass spectrometry (AMS) is a highly sensitive analytical methodology used to quantify the content of radioisotopes, such as 14 C, in a sample. The primary goals of this work were to demonstrate the utility of AMS in determining cellular [ 14 C]doxorubicin (DOX) concentrations and to develop a sensitive assay that is superior to high performance liquid chromatography (HPLC) for the quantification of DOX at the tumor level. In order to validate the superior sensitivity of AMS versus HPLC with fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…AMS has exhibited over five orders of magnitude higher sensitivity for detection of radiocarbon-labelled Adriamycin compared to other routinely-used assays such as HPLC (48). DNA adduct studies with many DNA binders have also demonstrated linear dose responses using AMS detection (31).…”
Section: Discussionmentioning
confidence: 99%
“…AMS has exhibited over five orders of magnitude higher sensitivity for detection of radiocarbon-labelled Adriamycin compared to other routinely-used assays such as HPLC (48). DNA adduct studies with many DNA binders have also demonstrated linear dose responses using AMS detection (31).…”
Section: Discussionmentioning
confidence: 99%
“…FTICR может provide a detection limit of approximately 30 zmol (≈ 18 000 molecules) for proteins with molecular weights ranging from 8 to 20 kDa [64]. To date the detection limit for accelerator massspectrometry in different analytical protocols is not as low as femtomolar [65,66] and attomolar [67,68], but even subattomolar [69] and zeptomolar [70][71][72] concentrations, corresponding to the sensitivity at the atomic level and satisfying the trend to the «accelerator mass spectrometryisotope measurements at the atomic level» [72]. Thus, the accuracy of MS-patch-clamp analysis can be significantly improved with the implementation of «accelerator MSpatch-clamp» concept.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers used AMS to quantify total cellular 14 C-anthracycline concentrations, following administration of doxorubicin, an anthracycline chemotherapeutic agent [55]. Two different mouse models were used:…”
Section: Preclinical Pharmacologymentioning
confidence: 99%